Lipoprotein-biomimetic nanostructure enables efficient targeting delivery of siRNA to Ras-activated glioblastoma cells via macropinocytosis - Jia-Lin Huang (Nature Portfolio, 2017)
Drug delivery in brain tumours is still a significant clinical concern. In this study, the authors develop a biomimetic lipoprotein nanoparticle for the efficient delivery of ATF5 siRNA inRas-activated brain cancer cells, where the nanoparticle is internalized by macropinocytosis in a Ras-dependent manner.